Peran Notaris Sebagai Pembuat Akta Otentik dalam Proses Pembuktian di Pengadilan. - Sihaan, Ade Yuliani; Hasanah, Aida Nur (Universitas Islam Negeri Sumatera Utara Medan, 2023)
ABSTRACT : Notaries as public officials who have the authority to make authentic deeds, in carrying out their duties are also attached to obligations that must be obeyed, because these obligations are something that must be carried out. What is questioned is what is the role of the notary in making authentic deeds in accordance with the regulations in force in Indonesia and what is the role of the notary as an authentic deed maker in the trial of evidence in court. This study uses normative research methods with data collection techniques, namely literature studies with conclusions drawn using deductive methods. The provisions in article 66 (1) of Law No. 2 years 2014 about the change of law No. 30 years 2004 regarding the Office of Notary states that in essence that in the interest of the judicial process, investigators, public prosecutors, or judges through the approval of the MPD have the authority to take photocopies of Minutes of Deeds and / or all letters which are one unit of Minutes of Deeds or Notary Protocols in Notary storage; and summon the Notary to attend for examination regarding the deed drawn up by the notary or the Notary Protocol kept by the Notary. Information from a notary as a witness in a criminal case is needed to explain the deed he made relating to the legal events explained by the appearer. Meanwhile, the notary's statement as a suspect is needed in relation to the notary's accountability for the authentic deed which is his responsibility. Based on this, it can be said that a notary as a citizen is not above the law. KEYWORDS : Notary, Authentic Deed, Court Evidence